The Impact of Environmental Awareness, Service Quality, Destination Attractiveness, Visitor Satisfaction, and Behavioral Intention on the Sustainability of Marine Ecotourism: A Case Study of the South Coast of West Java - Tri Widayati (Westscience Press, 2024)
This study examines the impact of environmental awareness, service quality, destination attractiveness, visitor satisfaction, and behavioral intention on the sustainability of marine ecotourism in the South Coast of West Java. A quantitative approach was employed, using structured questionnaires distributed to 312 tourists at various marine ecotourism sites. The data were analyzed using descriptive statistics, confirmatory factor analysis (CFA), and structural equation modeling (SEM). The results revealed significant relationships between environmental awareness, service quality, and destination attractiveness with visitor satisfaction and behavioral intention, which, in turn, positively affected the sustainability of marine ecotourism. The study highlights the critical role of fostering environmental awareness and improving service quality and destination appeal in promoting sustainable tourism practices. These findings offer practical recommendations for stakeholders, including policymakers and tourism operators, aiming to enhance the sustainability of marine ecotourism in the region.